Uji Efektivitas Anti-Aging Ekstrak Bunga Kembang Sepatu (Hibiscus rosa-sinensis L.) Dalam Sediaan Masker Clay - Tetty Noverita Khairani; Khairani Fitri; Luthvia Luthvia; Leny Leny; Faizah Rahman (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Skin aging is a natural degenerative process triggered by internal and external factors, particularly oxidative stress caused by free radicals. Hibiscus rosa-sinensis L. contains flavonoid and anthocyanin compounds which have potential as natural antioxidants to inhibit the skin aging process. Objective: This study aimed to formulate and evaluate a clay mask containing ethanol extract of Hibiscus rosa-sinensis flowers and to test its anti-aging effectiveness on skin condition parameters. Methods: This experimental study involved the preparation of clay masks with three variations of extract concentrations: 2.5% (F1), 5% (F2), and 10% (F3). Physical quality evaluations included homogeneity, pH, stability, drying time, emulsion type, and irritation tests. Anti-aging effectiveness testing was conducted on 15 female volunteers aged 35–60 years using a skin analyzer over 4 weeks with once-weekly application. Measured parameters included moisture, evenness, pore size, spots, and wrinkles. Data were analyzed using the Kruskal-Wallis test followed by the Mann-Whitney test. Results: All formulas met the physical quality requirements with pH values of 6.4–6.7, homogeneous, stable during 12 weeks of storage, and caused no irritation. Formula III (10% concentration) demonstrated the best anti-aging effectiveness with increases in moisture content of 67.5%, decreases in roughness of 42.3%, decreases in pore size of 30.9%, decreases in spots of 32.4%, and decreases in wrinkles of 36.0% after 4 weeks of treatment. However, the effectiveness of Formula III remained lower than that of the commercial clay mask. Conclusion: Ethanol extract of Hibiscus rosa-sinensis can be formulated as a stable and safe anti-aging clay mask. The 10% concentration formula exhibited the best effectiveness in improving skin aging parameters, although further formula optimization is still required to approach the effectiveness of commercial products.